The European Patent with Unitary Effect – a Unitary Patent Protection for a Unitary Market? - Katharina Kaesling (UCL Journal of Law and Jurisprudence, 2015)
As patent protection is in principle attributed on a national level, it is susceptible to create a fragmented EU market and barriers to the free movement of goods. A purely national patent law and policy do therefore not mirror the objective of an EU Internal Market. In December 2012, the EU legislator adopted Regulation No 1257/2012 implementing enhanced cooperation in the area of the creation of unitary patent protection. Rather than drawing up a Regulation covering comprehensively the substantive law of the unitary patent, the Regulation arranges for a multi-layer patent protection consisting of public international law, especially the European Patent Convention, diverse national laws of the Member States and the Regulation itself. This leads to legal uncertainty and confusion. The Regulation brings about some advancement for the free movement of goods by eliminating national markets where products can be marketed without EU-wide exhaustion and by aligning acquisition, limitation, revocation and lapse throughout the participating Member States. Regrettably, the concept is not carried through in the area of licensing, which remains one of the neuralgic points of the area of tension between patent rights and the free movement of goods. Read more